Jalal AL-deen ALhanafi and his educational effect on the IRAQI society - A historical study - انوار ناصر حسن (College of Education for Women, 2019)
Sheikh Hanafi was born in one of the popular shops of Baghdad with interlocking social relations, and had a profound impact this camp where his talents in the first Venco loving to Mahalah and Baghdad and was born with this development since his days looked forward to the folklore and folk. In the middle of his youth, including authoring loves the heritage of folk legacies began in motion, from Baghdad, books, articles, research has brought him wide acclaim were not possible without the seriousness and diligence, independence and self-Asamath that mushroom on them The trip was one of his tools in the scientific fame has gone to many Eastern and Asian countries and visited religious and literary institutes and delivered the lectures and increased the seconded to teach Arabic language schools in China and in the meantime, to learn Chinese, we mean that the impact of the Hanafi was not limited in their homeland, but also extended to where he was deported and it established a milestone or diligent in spreading his knowledge Hanafi did not seek in this long march towards hoarding money or the pursuit of self-merit but his goal was essential is saying the right and the statement of facts in the vague issues in literature, religion and society has succeeded in all that Finally, the Hanafi was a model of the mind of all Iraqis Iraqi meanings open to different perspectives he had any knowledge about his research and a disciplined awareness outside thenarrow boundaries of nationalism or hateful sectarian, tribal and all that violates Iraqi general nature of the tolerant and kind In this Hanafi he gave a lesson in humanity in the movement of his life from childhood to the last moment of his life. His message was so clear-cut in all his manifold in science and knowledge as a man of religion and a poet, writer and preacher, critic, social reformer and breeders objective